Culture, Travels and National Identity in Transylvania in the Aftermath of the Great War - TĂTAR-DAN, Maria (Studia Universitatis Babeș-Bolyai Historia, 2024)
In the aftermath of the Great War, the Kingdom of Romania significantly expanded its territory and population by incorporating Transylvania, Bessarabia, and Bucovina. Despite the enthusiasm that accompanied the “Great Union”, integrating these culturally distinct areas proved to be a complex and challenging process. Alongside political and administrative unification, the Romanian state faced the task of bringing together populations with different histories and cultural backgrounds. This integration involved not only formerly dominant ethnic groups but also Romanians who had lived and defined themselves as a national community within different contexts. Various debates emerged among the Romanian elites regarding the means of achieving cultural and spiritual unity. One of the factors perceived as hindering the profound unification was the fact that the Romanians from the Old Kingdom and those from the newly acquired provinces were unfamiliar with each other’s culture, habits and customs. Although cultural contacts and transfers had indeed existed before the war, the new context necessitated broader engagement, and the ties needed to be extended to a larger segment of the population. One suggested solution was to promote tourism and travel between the Old Kingdom and the new provinces, so as to foster better understanding, familiarity, and unity among Romanians. By examining journal articles, travel notes and memoirs, the main issue addressed by the present paper is the manner in which tourism and travel fostered cultural and social bonds among Romanians from different areas of Greater Romania, reinforcing a shared sense of national identity. Rezumat: La sfârşitul Marelui Război, Regatul României şi-a extins semnificativ teritoriul şi populaţia prin încorporarea provinciilor Transilvania, Basarabia şi Bucovina. Deşi aceste provincii aveau o populaţie majoritar românească, ele erau dominate politic, cultural şi economic de alte grupuri etnice. În pofida entuziasmului „Marii Uniri”, integrarea acestor zone cu o istorie şi culturi diferite s-a dovedit a fi un proces complex şi plin de provocări. Chiar şi comunităţile româneşti din aceste regiuni trăiseră şi se definiseră ca şi comunitate naţională în contexte diferite. Anii de debut ai perioadei interbelici au fost marcaţi de dezbaterea privind mijloacele de realizare a integrării şi unificării spirituale a noilor provincii. Unul dintre factorii percepuţi ca fiind un obstacol în calea unităţii depline era faptul că românii din Vechiul Regat şi cei din provinciile nou dobândite nu sunt familiari unii cu alţii, nu îşi cunosc cultura, obiceiurile şi tradiţiile. Deşi contacte şi transferuri culturale au existat şi înainte de război, noul context al României Mari necesita un angajament mai larg, iar legăturile trebuiau extinse la un segment mai mare al populaţiei. Printre soluţiile propuse s-a aflat şi aceea a cunoaşterii reciproce, prin călătorii şi vizite de o parte şi de alta Carpaţilor, pentru a încuraja o mai bună înţelegere, familiaritate şi unitate în rândul românilor. Analizând articole de presă, note de călătorie şi memorii, prezenta lucrare abordează modul în care turismul şi călătoriile au stimulat legăturile culturale şi sociale între românii din diferitele regiuni ale României Mari, consolidând sentimentul de apartenenţă la aceeaşi comunitate naţională. Cuvinte cheie: România Mare, unificare, integrare, naţiune, cultură, Transilvania, călătorie, memorialistică. Article: history; Received: 04.09.2023; Revised: 10.11.2023 Accepted: 13.12.2023; Available online: 30.01.2024